Prolin, Asam Askorbat, dan Kandungan Air Relatif pada Tanaman C3 dan C4 yang Tercekam Kekeringan - selis meriem (Universitas Sulawesi Barat, 2020)
Drought stress reduces plant growth and development that even reduces crop productivity. Plants activate various physiological defense mechanisms against water stress. This study aimed to compare the contents of proline (Pro), abscisic acid (ABA), and relative water content (KAR) in the leaves tissue of C3 plants from spinach (Amaranthus hybridus) and C4 from water spinach (Ipomea reptana) during drought stress of 2 days, 4 days, 6 days, and 8 days. The parameters measured were the content of Pro, ABA, and KAR in both leaves of A. hybridus and I. reptana at each stress period. The results of the study showed that the concentration of Pro was higher in water spinach at 6 days and 8 days of drought stress and the highest KAR value at 8 days of drought stress. The highest proline was synthesized by I. reptana at the longest-term stress of 8 days (1.54 µmol proline/g leaf). While the highest KAR value was shown by A. hybridus, namely 1.00% at 8 days stress. The high value of Pro in I. reptana was a physiological response to the decrease of KAR value. The high ABA concentration in A. hybridus as much as 3878.12/100 g leaf samples is a strategy for C3 plants to reduce the transpiration rate. On the other hand, the C4 plant of I. reptana demonstrated a defense mechanism by increasing the Pro osmoregulator to balance the osmotic cells when the KAR value decreased under prolonged stress. Keywords— abscisic acid, C3, C4, proline, relative water content